Handling Global Warming With The Movement To Plant Trees In Terasbendung Village Communities - Firdaus Firdaus; Azef Rahmat Hary Sapto; Muhtasor Jidan; Hairul Afandi; Ratu Anggita Aprilia; Rara Anggraeni Nur Afifah; Regina Permatadewi Tantiany Gunawan; Mareta Puspita Arianie; Elly Nurmahlia; Andini Marwah; Rima Oktavian; Wafdaa Taaz Hafsari Putri; Belardo Prasetya Mega Jaya (MOVE: Journal of Community Service and Engagement, 2022)
Terasbendung Village is one of the villages in Lebakwangi district, Serang regency and is located in a lowland area with an area of rice farming land as the main commodity. The size of the farmland is not accompanied by shady areas so that the village environment becomes arid with weeds around the road. Related to this problem, the efforts made are with the DEMEN (Village Planting Tree) movement as a superior program. This program consists of four stages starting from the preparation stage with regional observation, the implementation stage, the implementation stage, and the evaluation stage. Trees planted include pulai trees, ambon trees, manga trees, and rambutan trees. Planting is carried out in the area around the road to the village starting from the Terasbendung village office with a total of 90 trees. This effort educates the public regarding the importance of trees in the environment and is expected to be a massive effort in the future. The movement of one tree for the world starting from the village will be able to develop into a massive movement for other regions as a model.